2017
DOI: 10.1108/jabs-08-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer behavior regarding luxury fashion goods in India based on the theory of planned behavior

Abstract: Purpose Even though the Indian luxury market is predicted to grow as much as the Chinese one over the coming years, limited research has been conducted on luxury consumer behavior. The purpose of this study is to examine the purchasing behavior for luxury fashion goods using the framework of the theory of planned behavior. Design/methodology/approach A total of 257 respondents were included after distributing a structured questionnaire by surveying real luxury consumers in Delhi. Data were analyzed using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 67 publications
11
93
5
3
Order By: Relevance
“…Jain et al [81] have reported that since a collectivist culture prevails in India, SN tends to have a greater impact on intention than Attitude, and this could hold true in this study. The study found that the demographic variables had statistically significant effects on some of the TPB constructs although such effects were weak.…”
Section: Synthesis Of the Major Findingssupporting
confidence: 53%
“…Jain et al [81] have reported that since a collectivist culture prevails in India, SN tends to have a greater impact on intention than Attitude, and this could hold true in this study. The study found that the demographic variables had statistically significant effects on some of the TPB constructs although such effects were weak.…”
Section: Synthesis Of the Major Findingssupporting
confidence: 53%
“…The higher the individual's purpose toward a particular behavior, the higher the probability that the response will be performed. The use of this theory on fashion industry has been carried out in several products, such as fashion counterfeits (Kim and Karpova, 2009;Fernandes, 2013), luxury goods (Phau, Teah, and Chuah, 2015;Jain, Khan, and Mishra, 2017;, green shoes and apparel (Nam, Dong, and Lee, 2017;Bong ko and Jin, 2017). Nam, Dong, and Lee (2017) modified the theory by providing expectation and perception variables following Tseng and Hung (2013) on green sportswear.…”
Section: Literature Review 21 the Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Perceived behavioral control refers to the level of difficulty a person feels when performing certain behaviors where the more opportunities and resources available to a person, the greater the individual's control over the behavior (Jain, et al 2017;Chen & Tung, 2014) will affect consumer intentions and behavior. PBC helps predict behavior that individuals want to do but cannot be done because of lack of opportunities and / or resources (e.g.…”
Section: Doesmentioning
confidence: 99%